La crisis del «partido castellano» y la transformación de la Monarquía Hispana en el cambio de reinado de Felipe II a Felipe III - Martínez Millán, José (Cuadernos de Historia Moderna, 2003)
Nowadays, the Historiography stands out the tax system increase in order to explain the dissociation produced among the King and the Kingdom at the end of 16th Century as a prelude of the decadence that Hispanic Monarchy lived during Philip’s III reign. From this point of view, the decadence is raised, unconsciously at least, as a degradation or descomposition of the structures established in times of Philip the second. This article tries to demonstrate that two Philips’ relief in the throne produced a deep transformation of the Monarchy¸ not only the principal social leaders changed but also the political-religious model was replaced with the catholic Roman paradigm which is supported a lot of time during the 17th century. Reaching this aim, the author looks the failed project of the China conquest and the strange behavior of the jesuit Alonso Sánchez, promoter of such an adventure.